RUMPUT LAUT Eucheuma denticulatum SEBAGAI FITOREMEDIATOR PERTUMBUHAN UDANG VANAME (Litopenaeus vannamei) - Wilmy Etwil Pelle; Adnan Wantazen; Suzanne Undap; Edwin LA Ngangi (JURNAL PESISIR DAN LAUT TROPIS, 2021)
The long-term goal of this research is the management of vaname shrimp culture that is certified "Good Fish Cultivation" (GFC) based on environmentally friendly and sustainable technology so that its products can be accepted in domestic and foreign markets. The specific target is the implementation of phytoremediation technology in shrimp aquaculture at the Marine Field Station owned by FPIK UNSRAT which will be developed into the North Sulawesi Marine Education Center (NSMEC) area. The long-term goals and specific targets above will support the leading areas of maritime and maritime affairs in the Unsrat Research Master Plan. Analysis of water quality parameters and shrimp growth response using controlled-scale phytoremediation technology was carried out to see the remediation ability of Eucheuma denticulatum seaweed. Research method using phytoremediation technology application on white shrimp cultivation in the form of demonstration plots. The average growth in the plots provided with seaweed ranged from 8.3 g to 8.4 g. While the control that was not stocked with seaweed, the average weight growth was 6.6 g. This figure shows quite different values for different treatments. Water quality parameters such as DO, pH showed better water quality conditions in the plots spread with seaweed. This shows that Eucheuma denticulatum seaweed is capable of being a phytoremediator for the environment where the vannamei shrimp (Litopenaeus vannamei) is present. Seaweed Eucheuma denticulatum has the ability to absorb waste such as the faces of white shrimp (Litopenaeus vannamei).Â Keywords: phytoremediation, seaweed, vaname shrimp, East Likupang.